Urban criminology: the city, disorder, harm and social control - Atkinson, Rowland (Routledge, Taylor & Francis Group, 2019)
Understand crime, understand the city -- Place and locality: neighbourhoods and crime -- Urban economies -- Governance and social control in the urban arena -- Policing, the police and social order in the city -- Urban violence -- Housing systems, housing tenure and the dis/orderly city -- The political economy of urban safety.